Electroanalytical determination of oxadiazon and characterization of its base-catalyzed ring-opening products - Garrido, E. Manuela (2013)
The electrochemical behavior of the hydrolysis products of oxadiazon was studied by cyclic and square-wave voltammetry using a glassy carbon electrode. Maximum currents were obtained at pH 12.8 in an aqueous electrolyte solution containing 30% ethanol and the current did not decrease with time showing that there was little adsorption of the reaction products on the electrode surface. The hydrolysis products of oxadiazon were identi®ed, after isolation and puri®cation, as 1-trimethylacetyl-2-(2,4-dichloro-5-isopropoxyphenyl)-2-ethoxycarbonylhydrazine (Oxa1) and 1-trimethylacetyl-2-(2,4-dichloro-5-isopropoxyphenyl) hydrazine (Oxa2) with redox potentials 0.6Vand 70.1V (vs. Ag=AgCl), respectively. Based on the electrochemical behavior of 1-trimethylacetyl-2-(2,4-dichloro-5-isopropoxyphenyl) hydrazine (Oxa2) a simple electroanalytical procedure was developed for the determination of oxadiazon in commercial products used in the treatment of rice crops in Portugal that contain oxadiazon as the active ingredient. The detection limit was 161074 M, the mean content and relative standard deviation obtained for seven samples of two different commercial products by the electrochemical method were 28.4 0.8% (Ronstar) and 1.9 0.2% (Ronstar GR), and the recoveries were 100.3 5.4% and 101.1 5.3 %, respectively.